Peran Program Merdeka Belajar dalam Meningkatkan Kemandirian Mahasiswa melalui Kampus Mengajar - Rusda Nita Nelly Manurung (Departement of Mathematics Education, 2022)
The background of this research is to prepare students to face social, cultural, world of work changes and rapid technological advances so that human competence must be prepared to be better prepared to face the challenges of the times. Higher education institutions are required to be able to design and carry out innovative learning processes so that students can achieve learning outcomes covering aspects of attitude, knowledge and skills optimally and always relevant. The independent campus is a program from the Republic of Indonesia's Ministry of Education, Culture, Research and Technology which offers Indonesian students and female students the opportunity to hone their abilities according to their talents and interests by going directly into the world of work. The goal of the independent campus is that this policy aims to encourage students to master various sciences as preparation for future careers. By participating in various programs provided, students are expected to be able to develop their potential according to their passion and talents flexibly. The teaching campus program provides opportunities to practice teaching skills as well as self-development. This research uses qualitative research methods based on literature review or library research. The results of the study say that the teaching campus program is a means of strengthening student character. It is hoped that the existence of the MBKM program can also help create students who are independent and ready to work in Indonesia.